Environmental bioethics and ecopedagogy: the task ahead - Sarmiento Medina, Pedro José (Acta Bioethica, 2013)
This paper attempts at recovering environmental responsibility as a strictly bioethical notion and, at the same time, renew the need for educational activities as the only viable strategy in the context of environmental protection. It examines some pedagogical strategies and provides grounding for conceptual guidelines on environmental education. As a conclusion, it points out that it is necessary to learn how to reach decisions in the long run, integrating economics, ecology, education and social development as key elements for a treatment of the topic at a local and regional levels; it is however necessary to créate an environmental culture inducing structural changes in collective and individual behavior. It is a cultural change relying upon ecopedagogics, which necessarily proposes new behaviors, tools and values reflected in attitudes and consisten lifestyles.